PENGARUH CORPORATE GOVERNANCE TERHADAP STRUKTUR MODAL - Budi Kurniawan (Universitas Bunda Mulia, 2017)
This study aimed to examine of the Corporate Governance effect on the Capital Structure on companies surveyed by CGPI in 2013-2014 by using the control variables of firm’s Dividend Pay Out Ratio (DPR), Profitability, Size, Growth, and Leverage.The data used in this research is secondary data in the form of financial statements and surveys index by using regression analysis. Research result showed that there is no influence between Corporate Governance on Capital Structure. The same results was shown for control variable Dividend PayOut Ratio (DPR), Profitability, Size, Growth, and Leverage effect on Capital Structure.Keywords: Corporate Governance, Dividend Pay Out Ratio (DPR), Profitability, Size, Growth, Leverage, and Capital Structure